IMPLEMENTASI PEMBELAJARAN STEAM BERBASIS PROJEK PADA MATERI ENERGI TERBARUKAN DI SMA KELAS X - Barus, Carolina Sri Athena; Wattimena, Herman Samuel; Jamaludin, Jamaludin; Batlolona, John Rafafy; Eveline, Erlin; Taihuttu, Jony (Universitas Pattimura, 2025)
This community service activity was conducted by lecturers from Universitas Pattimura at SMA Negeri 57 Central Maluku to introduce physics learning through a project-based STEAM approach. The focus was on renewable energy, implemented through a hands-on project of building gas-powered mini cars. Students were actively engaged in collaborative learning, which significantly enhanced their enthusiasm, creativity, and understanding of the concept of work. Evaluation showed the approach to be effective, though a longer project duration is recommended for optimal outcomes. This activity is expected to serve as a model for innovative science learning and to strengthen the partnership between universities and schools. Keywords: STEAM, Project, Higher- order thinking.